The Perception and Attitudes Toward Learning English as A Foreign Language of Grade 4 Students, Thailand - Witayanont, Kornkamol (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
The purpose of this research study was to identify whether there are significant relationship and differences in perception of and attitudes toward learning English as a foreign language (EFL) of Grade 4 low-scoring and high-scoring students at Witayanont School, Thailand. A total of 70 students were surveyed in this study. The instruments used to collect the quantitative data were Perception of learning questionnaire developed by Alkaff (2013) and Learning Attitudes Questionnaire by SIL International (Orwig, 1995). Correlational analysis using Pearson Product Moment Correlation Coefficient to determine the relationship between the research variables and Independent Samples t-test was used to determine the differences between the research variables. The research found that Grade 4 students had nearly positive perception and attitudes toward learning EFL, English as a foreign language, in both low-scoring and high-scoring groups. Also, the research found a significant, positive, strong correlation between perception of and attitudes toward learning EFL in low-scoring students, and a significant, positive, moderate correlation in high-scoring students. Moreover, the research revealed that there was no significant difference between perception of learning EFL in low-scoring and high-scoring students, and also no significant difference between attitudes toward learning EFL in both groups.